The Development of Endurance Exercise in Developing the Training of Students Athletes in Jepara (Journal of Physical Education Health and Sport, 2022)
Physical condition exercise has an important role to develop athletes' achievements, confidence, and readiness to face the challenges in exercise and competition. Thus, their physical conditions must be trained. In the field, coaches of the athletes must work harder to calculate and determine the accurate exercise program for the athletes. The processes require a longer time. This reality encouraged the researchers to develop the Latidan 21 application to facilitate the trainers in developing endurance exercise programs quickly and accurately. The researchers hope the program would be relevant to the capabilities of the athletes' skills and could improve the endurance of the PPAP athletes of the Jepara Regency. In this research, the researchers developed the product with Research Development model proposed by Gall, Borg, and Gall (1996) with some adjusted needs based on the real situations. The research subjects consisted of an IT professional, a software programmer from Semarang, an IT lecturer of Unisbang, a Karate practitioner, trainers of National Sports Week for Central Java Karate, the Division Chief of Achievement Training Center of Indonesian National Sports Committee in Jepara Regency, and the various sample tests. The applied instruments were a questionnaire with a Likert scale, expert evaluation, product validation sheet, and interview guidelines. The developed product for the trainers, the athletes, and the constructors of the Jepara Regency was expected to improve endurance performance and human resources.